Harnessing near-infrared light via S0 to T1 sensitizer excitation in a molecular photon upconversion solar cell. Issue 12 (7th March 2022) - Beery, Drake; Arcidiacono, Ashley; Wheeler, Jonathan P.; Chen, Jiaqi; Hanson, Kenneth
Abstract : An Osmium sensitizer and anthracene annihilator are incorporated into a metal ion linked multilayer photoanode that harnesses NIR light in an integrated triplet–triplet annihilation upconversion solar cell. Abstract : Integrating molecular photon upconversion via triplet–triplet annihilation (TTA-UC) directly into a solar cell offers a means of harnessing sub-bandgap, near infrared (NIR) photons and surpassing the Shockley–Queisser limit. However, all integrated TTA-UC solar cells to date only harness visible light. Here, we incorporate an osmium polypyridal complex (Os) as the triplet sensitizer in a metal ion linked multilayer photoanode that is capable of harnessing NIR light via S0 to T1 * excitation, triple energy transfer to a phosphonated bis(9, 10-diphenylethynyl)anthracene annihilator (A), TTA-UC, and electron injection into TiO2 from the upcoverted state. The TiO2 -A-Zn-Os devices have five-fold higher photocurrent (∼3.5 μA cm −2 ) than the sum of their parts. IPCE data and excitation intensity dependent measurements indicate that the NIR photons are harvested through a TTA-UC mechanism. Transient absorption spectroscopy is used to show that the low photocurrent, as compared to visible light harnessing TTA-UC solar cells, can be atributed to: (1) slow sensitizer to annihilator triplet energy transfer, (2) a low injection yield for the annihilator, and (3) fast back energy transfer from the upconverted state to the sensitizer. Regardless, these results serve as a proof-of-concept that NIR photons can be harnessed via an S0 to T1 * sensitizer excited, integrated TTA-UC solar cell and that further improvements can readily be made by remedying the performance limiting processes noted above.